Preferensi Loyalitas Wisatawan terhadap Destinasi Wisata Bahari di Provinsi Banten - Hasryningsih, Andi; Diposumarto, Ngadino Surip; Muharam, Hari (Universitas Negeri Padang, 2024)
The objectives of this research is to investigate tourists' loyalty preferences towards marine tourism destinations in Banten Province. Researchers have conducted a survey of 30 tourists by representing the main question in the form of tourists' considerations of factors or variables that allow for influence or attachment in tourism loyalty to visits to marine tourism destinations in Banten Province, Indonesia. The findings show that tourist loyalty is influenced by perceived value, tourism satisfaction, perceived risk, perceived quality and destination image. Perceived value and tourist satisfaction contribute significantly to tourist loyalty. In addition, reducing perceived risk will increase comfort and trust. Superior perceived quality and a positive destination image influence tourists' intentions to return and recommend the destination. It can be concluded that these factors can contribute to tourist loyalty. It is very important to increase loyalty through various preferences of people who have many interesting experiences with the tourist destinations they visit. Therefore, it can be concluded that these factors can contribute to tourist loyalty. It is very important to increase loyalty through various preferences of people who have many interesting experiences about the tourist destinations they have visited. This will be part of efforts to evaluate and improve the regional economy through the tourism sector